Analysis Of Village Fund Management In The Jayapura City Government Area - Kristhina R.I. Luluporo; Yosephina Ohoiwutun; Hiskia C.M Sapioper (PT FORMOSA CENDEKIA GLOBAL, 2023)
The objectives of this research are; 1) Describe and analyze the management of Village Funds in the Jayapura City area. 2) Describe and analyze the determinant factors that support and hinder the management of Village Funds in villages in the Jayapura City area and 3) Provide solutions in efforts to improve the management of village funds in the Jayapura City area. This research uses a qualitative approach, which is limited to efforts to reveal a problem or situation or event as it really is. The results of this study show that the planning stages for managing village funds in Jayapura City are in accordance with applicable regulations, administration activities where recording of village fund financial transactions has been carried out properly.